Acetylene selective hydrogenation catalyst and preparation method and application thereof

By regulating the types and number of oxygen-containing groups on the surface of the support, an efficient acetylene selective hydrogenation catalyst was prepared, which solved the problems of poor selectivity of existing catalysts and large amount of green oil production, and achieved high metal utilization, high performance and long life.

CN119680541AActive Publication Date: 2025-03-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311244774.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

The existing carbon two-selective hydrogenation catalyst has poor activity selectivity, making it difficult to meet the requirements of high metal utilization, high performance, and long life, and the amount of green oil is generated large.

Method used

By controlling the types and amounts of oxygen-containing groups on the surface of the support, an alumina support with oxygen-containing groups on the surface is prepared by combining palladium and other metal co-active components.

Benefits of technology

It improves the acetylene conversion and selectivity of the catalyst, reduces the amount of green oil generation, extends the service life of the catalyst, and achieves high metal utilization and high performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004469127390000101
    Figure BDA0004469127390000101
  • Figure BDA0004469127390000111
    Figure BDA0004469127390000111
  • Figure BDA0004469127390000121
    Figure BDA0004469127390000121
Patent Text Reader

Abstract

The invention provides an acetylene selective hydrogenation catalyst and a preparation method and application thereof. The catalyst can convert acetylene in C2 fraction into ethylene through selective hydrogenation. The catalyst comprises a main active component, an auxiliary active component and a carrier, distribution of metal active components is controlled by regulating and controlling the type, number and density of oxygen-containing groups of the carrier, the metal utilization rate is increased, meanwhile, the green oil generation amount is reduced, and better ethylene selectivity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and specifically relates to an acetylene selective hydrogenation catalyst and a preparation method and application thereof, in particular to a selective hydrogenation acetylene removal catalyst for carbon distillation in a cracking gas sequential separation process and an application thereof. Background Art

[0002] Petrochemical industry plays a huge role in the national economy and social development. With the continuous increase in market demand, the number and capacity of ethylene plants are gradually increasing. Ethylene, as the basic raw material of organic chemical industry, is mainly used to produce synthetic materials such as polyethylene, ethylene oxide, and ethylbenzene rubber. Since the carbon distillate produced by the cracking unit contains alkynes, trace amounts of alkynes have an impact on subsequent polymerization reactions, continuous production, and product quality. Most of the alkynes are usually removed by selective hydrogenation, and the requirements for carbon dihydrogenation catalysts are also constantly increasing. As an important role in producing qualified ethylene products and improving ethylene yields, the research and development and improvement of this catalyst are mainly carried out from three aspects: carrier, main active component, and auxiliary active component. At present, the research on the types of main active components and auxiliary active components and their crystal structures is relatively complete, and the types of carriers and surface modification methods are still to be developed.

[0003] Chinese patent CN102240565A discloses a carbon two selective hydrogenation catalyst and its preparation method. The catalyst comprises an inert substrate, an alumina coating and an active metal. Alumina slurry is sprayed on an inert substrate such as a silicon carbide ring, and the shell thickness of the eggshell catalyst is controlled by controlling the weight ratio of alumina dry powder to the inert substrate. After drying and calcining, the active component Pd and the auxiliary active component are loaded on the carrier. The catalyst has an inlet acetylene concentration of 0.5 mol%, a hydrogen-acetylene ratio of 1.6, and an air velocity of 10,000 hr. -1 The selectivity is about 40% under the conditions.

[0004] Chinese patent CN104096573A discloses a highly anti-coking carbon two selective hydrogenation catalyst and its application. The catalyst uses alumina with a bimodal pore structure distribution as a carrier, and uses Pd and Ni as active components, which are loaded into the small pores and large pores of the carrier respectively, wherein the active metal Ni is loaded using a microemulsion method, and the particle size is controlled so that it enters the large pores, which greatly reduces the degree of coking on the catalyst surface.

[0005] Chinese patent CN106925272A discloses a carbon diselective hydrogenation catalyst. The catalyst uses a carbon material doped with B and O as a carrier, which changes the chemical activity of the carrier surface, enhances the interaction between the carrier and the metal particles, and is beneficial to the dispersion of the active component Pd particles. Compared with the Al2O3 carrier, the catalyst prepared using the carrier has low green oil generation and can operate stably for a long period of time.

[0006] In the existing technical solutions, the selectivity of the C2 selective hydrogenation catalyst and the controllability of the distribution thickness of the active metal on the carrier are poor, the amount of green oil generated is large, and it is difficult to achieve the requirements of high metal utilization, high performance and long life. The present invention improves the performance of the C2 selective hydrogenation catalyst prepared by using the carrier by controlling the type and number of oxygen-containing groups on the surface of the carrier. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention proposes a novel carbon two fraction selective hydrogenation catalyst, which is used for the selective hydrogenation of carbon two fractions to convert acetylene into ethylene.

[0008] One of the purposes of the present invention is to provide an acetylene selective hydrogenation catalyst, comprising: 100 parts of a carrier, 0.01-0.1 parts of a main active component, and 0.01-0.15 parts of an auxiliary active component, wherein the carrier surface contains 18-150 mmol / g of oxygen-containing groups, the main active component is Pd, and the auxiliary active component is at least one of Ga, Fe, Ni, As, Bi, Pb, Sn, Mn, and Ag. The auxiliary active component can be a metal auxiliary active component commonly used in the art, and in addition to the metal elements listed above, other commonly used active metal elements can also be used, such as rare earth metals, alkali metals, alkaline earth metals, etc.

[0009] According to the present invention, in the acetylene selective hydrogenation catalyst:

[0010] The catalyst comprises: 10,000 parts of a carrier, 0.02 to 0.05 parts of a main active component, and 0.1 to 0.1 parts of an auxiliary active component;

[0011] The carrier contains aluminum oxide and a carbonaceous component. Preferably, the carbonaceous component accounts for 0.1 to 20 wt % of the total weight of the carrier.

[0012] According to the present invention, in the acetylene selective hydrogenation catalyst:

[0013] The carrier contains abundant oxygen-containing groups, and the oxygen-containing groups are at least one of hydroxyl groups, carboxyl groups, and lactone groups. Preferably, the content of the hydroxyl groups is 3 to 60 mmol / g, preferably 12 to 50 mmol / g; the content of the carboxyl groups is 3 to 50 mmol / g, preferably 10 to 40 mmol / g; and / or the content of the lactone groups is 3 to 40 mmol / g, preferably 3 to 20 mmol / g;

[0014] The density of the surface oxygen-containing groups is 0.6 to 8 mmol / m 2 , preferably 0.8 to 5 mmol / m 2 ;

[0015] The specific surface area of ​​the carrier is 5 to 260 m 2 / g, water absorption rate is 40-120%, carrier strength is 50-80N / particle, bulk density is 0.6-0.9g / ml, pore volume is 0.4-1.2ml / g.

[0016] The second object of the present invention is to provide a method for preparing the above-mentioned acetylene selective hydrogenation catalyst, comprising: fully mixing a solution containing a metal compound of a main active component and a metal compound of an auxiliary active component with a carrier, and then molding, drying and calcining to obtain the acetylene selective hydrogenation catalyst.

[0017] According to the present invention, in the method for preparing the acetylene selective hydrogenation catalyst:

[0018] The metal compound of the main active component is selected from at least one of soluble compounds of palladium, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate;

[0019] The metal compound of the auxiliary active component is selected from at least one of chlorides, nitrates, acetates, sulfates, and metal organic compounds of Ga, Fe, Ni, As, Bi, Pb, Sn, Mn, and Ag;

[0020] The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohols.

[0021] According to the present invention, in the method for preparing the acetylene selective hydrogenation catalyst:

[0022] The main active component and the auxiliary active component can be loaded onto the carrier by any method for preparing a supported catalyst in the art. For example, the loading method includes loading the active component precursor compound onto the carrier by spraying and / or impregnation.

[0023] The drying conditions are: drying at 60-150°C for 2-12 hours, preferably, drying at 70-140°C for 4-10 hours;

[0024] The calcination conditions are: 200-1500° C. for 2-12 h, preferably 300-1300° C. for 4-10 h.

[0025] According to the present invention, the carrier is obtained by the following preparation method: the aluminum source, the forming agent, the pore expanding agent and the functional carbon are fully mixed, the binder is added, kneaded into a shape, dried, and then surface treated to obtain the carrier.

[0026] According to the present invention, in the method for preparing the carrier:

[0027] The aluminum source is selected from at least one of boehmite, pseudo-boehmite, γ-alumina, α-alumina, θ-alumina, and aluminum hydroxide;

[0028] The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch;

[0029] The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol;

[0030] The functional carbon is selected from at least one of coke, activated carbon, carbon black, white carbon, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond;

[0031] The binder is selected from a solution of at least one of nitric acid, sulfuric acid, hydrochloric acid, oxalic acid, acetic acid, citric acid, and ascorbic acid, and the solvent in the solution is selected from at least one of water, ethanol, ethylene glycol, and ethylenediamine;

[0032] The amount of the functional carbon is 1 to 40 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the contained Al2O3;

[0033] The amount of the forming agent used is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained;

[0034] The amount of the pore expanding agent used is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the contained Al2O3.

[0035] According to the present invention, in the method for preparing the carrier:

[0036] The carrier can be formed by any existing forming technology in the art, such as at least one of fluidized granulation, agglomeration granulation, extrusion granulation, compression granulation or spray granulation;

[0037] Before the surface treatment, the granulated material is first dried. The drying process can adopt the drying equipment and drying conditions commonly used in the prior art. For example, the drying conditions are: drying at 60-160° C. for 4-12 hours, preferably, drying at 80-140° C. for 6-10 hours;

[0038] The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation. During the preparation of the carrier, the crystal structure, surface isoelectric point, and local Al-O charge density are changed by surface treatment, introduction of carbon species, and the like to increase the types and quantity of oxygen-containing groups in the carrier, wherein:

[0039] The heat treatment conditions are as follows: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa;

[0040] The crystallization conditions are: temperature 120-250° C., time 4-18 h, pressure 0.2-15 MPa, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine;

[0041] The oxidation conditions are as follows: temperature 30-80° C., time 0.2-10 h, the oxidant solution used for oxidation is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L;

[0042] The alkalization conditions are: temperature 30-110° C., time 0.2-10 h, the alkaline solution used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline solution is 0.1-10 mol / L;

[0043] The irradiation conditions are: the ray source is selected from gamma rays and / or microwaves, preferably, the gamma ray irradiation dose rate is 1-90 kGy / min, the time is 0.2-24 h; and / or the microwave power is 50-1000 W, the time is 0.5-60 min.

[0044] In the present invention, the alumina carrier and its preparation can refer to Patent ZL202311028071.8, and the relevant contents disclosed in the aforementioned document are introduced into the present invention as a reference.

[0045] The third object of the present invention is to provide an application of the above-mentioned acetylene selective hydrogenation catalyst or the acetylene selective hydrogenation catalyst obtained by the above-mentioned preparation method in the selective hydrogenation reaction of carbon two fractions, wherein the "selective hydrogenation of carbon two fractions" refers to the process of converting acetylene into ethylene by selective hydrogenation.

[0046] According to the present invention, in the hydrogenation reaction, the molar ratio of H2 to alkynes in the carbon distillation raw material is (1.2-2):1, preferably (1.3-1.6):1; the conditions of the hydrogenation reaction include: the reactor inlet temperature is 25-85°C, the reactor pressure is 0.5-3.2MPa, the reaction space velocity is 2000-12000h-1 .

[0047] The present invention adopts an alumina carrier rich in oxygen-containing groups on the surface to prepare an acetylene selective hydrogenation reaction catalyst. Compared with the commonly used alumina in the prior art, the alumina carrier can better interact with the precious metal palladium. By adjusting the type and amount of oxygen-containing groups on the carrier, the dispersion of the precious metal is improved, and the utilization rate of the metal active components is improved, so that the prepared catalyst can provide more acetylene adsorption and hydrogen dissociation sites, thereby improving the acetylene conversion rate and selectivity while reducing the amount of green oil generated, thereby extending the service life of the catalyst. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0049] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0050] Example 1

[0051] 1. Preparation of molding carrier

[0052] Weigh 100 g of pseudo-boehmite (specific surface area 195.6 m 2 / g, pore volume 0.69ml / g, bulk density 0.23g / ml), 3g starch, 3 polyethylene glycol cellulose, 7g graphene, put into a kneader and mix evenly. Weigh 3g concentrated sulfuric acid and add 110ml deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead and extrude into pellets to obtain cylindrical particles with a particle size of 2-4mm. After crystallization in 1MPa, 250℃ water for 10h, heat treat with carbon dioxide and air (volume ratio of 0.5:1) at 1100℃, 0.4MPa for 3h, then immerse in 30℃, 1.5mol / L potassium permanganate for 3h, and finally dry at 100℃ for 10h to obtain alumina carrier S1.

[0053] 2. Preparation of Selective Hydrogenation Catalyst

[0054] 0.03 g of silver nitrate and 0.07 g of gallium nitrate were weighed and added to 8 mL of palladium nitrate solution (Pd content was 5 mg / mL), diluted to 63.2 mL with deionized water, and sprayed onto 100 g of alumina support S1. The sprayed sample was placed in an oven and dried at 130° C. for 8 h and then calcined at 500° C. for 10 h to obtain catalyst C1, whose Pd loading was 0.04 wt%, Ag loading was 0.02 wt%, and Ga loading was 0.02 wt%.

[0055] Example 2

[0056] 1. Preparation of molding carrier

[0057] Weigh 100g of pseudo-boehmite in Example 1, 4g of sesbania powder, 3g of polyacrylamide, and 8g of glassy carbon, put them into a kneader and mix them evenly. Weigh 2g of concentrated nitric acid and 1g of citric acid, add them to 120g of deionized water, mix them evenly to prepare a mixed solution. Add the prepared solution into a kneader, knead it, extrude it into pellets, and obtain cylindrical particles with a particle size of 2-4mm. Crystallize it in water at 150℃ and 0.5MPa for 5h, dry it at 130℃ for 6h, soak it in a potassium citrate solution at 40℃ and 1.5mol / L for 3h, dry it at 100℃ for 10h, and irradiate it with 3kGy / min of gamma rays for 5h to obtain an alumina carrier S2.

[0058] 2. Preparation of Selective Hydrogenation Catalyst

[0059] 0.29 g of gallium nitrate was weighed and added to 8 mL of palladium nitrate solution (Pd content was 5 mg / mL), diluted to 52.1 mL with deionized water, and sprayed onto 100 g of alumina carrier S2. The sprayed sample was placed in an oven and dried at 130° C. for 8 h and then calcined at 500° C. for 10 h to obtain catalyst C2, whose Pd loading was 0.04 wt% and Ga loading was 0.08 wt%.

[0060] Example 3

[0061] 1. Preparation of molding carrier

[0062] Weigh 100g of pseudo-boehmite in Example 1, 2g of carboxyethyl cellulose, 3g of starch, and 6g of bamboo charcoal, put them into a kneader and mix them evenly. Weigh 3g of oxalic acid and add it to 115g of deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead it, extrude it into pellets, and obtain cylindrical particles with a particle size of 2-4mm. After drying at 100℃ for 10h, heat treat it with 1000℃, 1MPa of ethylene and nitrogen (volume ratio of 0.8:1) for 5h, soak it in 60℃, 2mol / L sodium carbonate solution for 3h, and finally irradiate it with 200w microwave for 30min to obtain alumina carrier S3.

[0063] 2. Preparation of Selective Hydrogenation Catalyst

[0064] 0.07 g of gallium nitrate and 0.19 g of bismuth nitrate were weighed and added to 8 mL of palladium nitrate solution (Pd content was 5 mg / mL), diluted to 46.2 mL with deionized water, and sprayed onto 100 g of alumina carrier S3. The sprayed sample was placed in an oven and dried at 130° C. for 8 h and then calcined at 500° C. for 10 h to obtain catalyst C3, whose Pd loading was 0.04 wt%, Ga loading was 0.02 wt%, and Bi loading was 0.08 wt%.

[0065] Example 4

[0066] 1. Preparation of molding carrier

[0067] Weigh 100g of pseudo-boehmite in Example 1, 6g of carboxymethyl cellulose, 2g of polyvinyl alcohol, and 5g of activated carbon, put them into a kneader and mix them evenly. Weigh 4g of acetic acid and add it to 120g of deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead it, extrude it into pellets, and obtain cylindrical particles with a particle size of 2-4mm. After drying at 110℃ for 5h, heat treat it with 1150℃, 1MPa of carbon dioxide and argon (volume ratio of 0.1:1) for 5h, soak it in 50℃, 2mol / L ascorbic acid solution for 2h, and finally irradiate it with 1.5kGy / min of gamma rays for 2h to obtain alumina carrier S4.

[0068] 2. Preparation of Selective Hydrogenation Catalyst

[0069] 0.29 g of ferric nitrate and 0.06 g of silver nitrate were weighed and added to 8 mL of palladium nitrate solution (Pd content was 5 mg / mL), diluted to 54.9 mL with deionized water, and sprayed onto 100 g of alumina carrier S4. The sprayed sample was placed in an oven and dried at 130° C. for 8 h and then calcined at 500° C. for 10 h to obtain catalyst C4, whose Pd loading was 0.04 wt%, Fe loading was 0.04 wt%, and Ag loading was 0.04 wt%.

[0070] Example 5

[0071] 1. Preparation of molding carrier

[0072] Weigh 100g of pseudo-boehmite in Example 1, 3g of sesbania powder, 3g of methyl cellulose, and 6g of white carbon black, put them into a kneader and mix them evenly. Weigh 2g of concentrated nitric acid and add it to 115g of deionized water to prepare a mixed solution. Add the prepared solution into a kneader, knead it, extrude it into pellets, and obtain cylindrical particles with a particle size of 2-4mm. Crystallize it in ethanol at 130℃ and 1MPa for 6h, then dry it at 130℃ for 6h, then soak it in a 40℃, 2mol / L ammonium persulfate solution for 3h, and finally irradiate it with 300w microwave for 20min to obtain alumina carrier S5.

[0073] 2. Preparation of Selective Hydrogenation Catalyst

[0074] 0.15 g of ferric nitrate and 0.07 g of gallium nitrate were weighed and added to 8 mL of palladium nitrate solution (Pd content was 5 mg / mL), diluted to 48.7 mL with deionized water, and sprayed onto 100 g of alumina carrier S5. The sprayed sample was placed in an oven and dried at 130° C. for 8 h and then calcined at 500° C. for 10 h to obtain catalyst C5, whose Pd loading was 0.04 wt%, Fe loading was 0.02 wt%, and Ga loading was 0.02 wt%.

[0075] Example 6

[0076] 1. Preparation of molding carrier

[0077] The carrier preparation was the same as in Example 1.

[0078] 2. Preparation of Selective Hydrogenation Catalyst

[0079] 0.08 g of ferric nitrate and 0.1 g of bismuth nitrate were weighed and added to 9 mL of palladium nitrate solution (Pd content was 5 mg / mL), diluted to 48.7 mL with deionized water, and sprayed onto 100 g of alumina support S1. The sprayed sample was placed in an oven and dried at 130 ° C for 8 h and then calcined at 500 ° C for 10 h to obtain catalyst C6, whose Pd loading was 0.045 wt%, Fe loading was 0.01 wt%, and Bi loading was 0.04 wt%.

[0080] Comparative Example 1

[0081] The catalyst was prepared by using S1 as a carrier. Unlike the catalyst C1, no auxiliary active component was added and the Pd loading was 0.05 wt %, thereby obtaining the catalyst D1.

[0082] Comparative Example 2

[0083] The carrier was prepared according to the method of Example 1, except that graphene was not added during the molding process, and other treatment methods remained unchanged to obtain carrier S6. The catalyst preparation method was the same as that of Example 1 to obtain catalyst D2.

[0084] Comparative Example 3

[0085] The carrier was prepared according to the method of Example 1, except that the pellets were calcined in a muffle furnace at 1200° C. for 5 h after being cut and dried, to obtain carrier S7. The catalyst was prepared in the same manner as in Example 1 to obtain catalyst D3.

[0086] Comparative Example 4

[0087] Take the commercially available carrier with a specific surface area of ​​70.4m 2 / g, bulk density of 0.65g / ml, strength of 43.7Nm, and water absorption rate of 52.6% finished alumina was used as carrier S8, and the catalyst preparation method was the same as that in Example 1 to obtain catalyst D4.

[0088] Comparative Example 5

[0089] The commercially available carrier S8 was used to prepare a catalyst according to the method of Comparative Example 1 to obtain catalyst D5.

[0090] The test instruments and test conditions used in the embodiments and comparative examples are as follows:

[0091] The specific surface area was measured by nitrogen physical adsorption BET method;

[0092] The bulk density was calculated by measuring the mass of 100 mL of alumina support, and the average value was taken after measuring each sample three times;

[0093] The strength was measured using a universal particle strength measuring instrument, and the average value of the measurement results of 20 carrier particles was taken;

[0094] The water absorption rate is obtained by taking 20 g of the alumina carrier, immersing it in water for 10 minutes, taking it out and draining the surface water, and measuring the weight increase.

[0095] The nature and quantity of oxygen-containing groups in the carrier were determined by Boehm chemistry.

[0096] The dispersion was determined by chemical adsorption method.

[0097] Table 1. Physical property measurement results of alumina carriers in Examples and Comparative Examples

[0098]

[0099] The oxygen-containing groups of the carriers of the embodiments and comparative examples were analyzed and determined. Three portions of 0.6 g of the carrier were weighed and soaked in 40 ml of 0.05 mol / L NaHCO3, Na2CO3 and NaOH solutions for 24 h, respectively. 10 ml of the soaked solution was titrated with 0.05 mol / L hydrochloric acid. Each sample was titrated three times, and the arithmetic mean was taken. The number of various oxygen-containing groups of the carrier was calculated based on the consumption of alkali, and the oxygen-containing group density was obtained in combination with the carrier specific surface data. The results are listed in Table 2.

[0100] Table 2. Measurement results of oxygen-containing groups on alumina supports of Examples and Comparative Examples

[0101]

[0102] It can be seen from Table 2 that the content and density of oxygen-containing groups on the surface of the alumina support prepared by the method of the present invention are significantly higher. At the same time, by adjusting the raw material ratio, preparation process parameters and conditions, the method of the present invention can achieve the regulation of the number and distribution of oxygen-containing groups on the surface of the alumina support.

[0103] Test Case

[0104] 10 ml of the catalyst in the above examples and comparative examples were respectively added into an adiabatic fixed bed reactor and evaluated under the following conditions. The evaluation results are shown in Table 3.

[0105] The component contents of the carbon distillation raw material and the material after selective hydrogenation using various catalysts were detected by gas chromatography, and the ethylene selectivity and conversion rate were calculated according to the following formula.

[0106] Ethylene selectivity = (ethylene out - Vinyl in ) / (Acetylene in -Acetylene out )*100%

[0107] Ethylene conversion = (acetylene out -Acetylene in ) / Acetylene in *100%

[0108] Evaluation conditions are: C2 fraction feedstock is fed into the selective hydrogenation reactor from top to bottom, reactor inlet temperature is 50°C, pressure is 1.0 MPa, reactor feedstock composition (molar fraction) is: ethane 7.02%, ethylene 91.94%, acetylene 0.43%, hydrogen 0.61%, reaction space velocity 8000 hr -1 .

[0109] Table 3. Catalytic performance evaluation results of catalysts

[0110]

[0111] The contents of alkyne and olefin components in the hydrogenated products in Table 3 are the weight percentages calculated after deducting the hydrogen content. It can be seen from the results in Table 3 that, compared with Comparative Examples 1 to 5, the metal active components in Examples 1 to 6 have a higher dispersion on the carrier, indicating that the oxygen-containing groups on the surface of the carrier can improve the uniformity of the metal loading; in addition, the results of the selective hydrogenation of the carbon distillate above show that the catalysts prepared by Examples 1 to 6 of the present invention exhibit more excellent catalytic performance, better selectivity, and higher catalytic utilization of metal atoms.

Claims

1. An acetylene selective hydrogenation catalyst comprising: 100 parts of a carrier, 0.01 to 0.1 parts of a main active component, and 0.01 to 0.15 parts of an auxiliary active component, wherein the surface of the carrier contains 18 to 150 mmol / g of oxygen-containing groups, the main active component is Pd, and the auxiliary active component is at least one of Ga, Fe, Ni, As, Bi, Pb, Sn, Mn, and Ag.

2. The acetylene selective hydrogenation catalyst according to claim 1, characterized in that The catalyst comprises: 100 parts of a carrier, 0.02 to 0.05 parts of a main active component, 0.01 to 0.1 parts of an auxiliary active component; and / or, The carrier contains aluminum oxide and a carbonaceous component. Preferably, the carbonaceous component accounts for 0.1 to 20 wt % of the total weight of the carrier.

3. The acetylene selective hydrogenation catalyst according to claim 1, characterized in that The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group. Preferably, the content of the hydroxyl group is 3 to 60 mmol / g, and / or the content of the carboxyl group is 3 to 50 mmol / g, and / or the content of the lactone group is 3 to 40 mmol / g; and / or, The density of the surface oxygen-containing groups is 0.6 to 8 mmol / m 2 , preferably 0.8 to 5 mmol / m 2 and / or, The specific surface area of ​​the carrier is 5 to 260 m 2 / g, water absorption rate is 40-120%, carrier strength is 50-80N / particle, bulk density is 0.6-0.9g / ml, pore volume is 0.4-1.2ml / g.

4. A method for preparing the acetylene selective hydrogenation catalyst according to any one of claims 1 to 3, comprising: The acetylene selective hydrogenation catalyst is obtained by fully mixing a solution containing a metal compound of a main active component and a metal compound of an auxiliary active component with a carrier, and then molding, drying and calcining the mixture.

5. The preparation method according to claim 4, characterized in that: The metal compound of the main active component is selected from at least one of soluble compounds of palladium, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate; and / or, The metal compound of the auxiliary active component is selected from at least one of chlorides, nitrates, acetates, sulfates and metal organic compounds of Ga, Fe, Ni, As, Bi, Pb, Sn, Mn and Ag; and / or, The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohols; and / or, The drying conditions are: drying at 60-150°C for 2-12 hours, preferably, drying at 70-140°C for 4-10 hours; and / or, The calcination conditions are: 200-1500° C. for 2-12 h, preferably 300-1300° C. for 4-10 h.

6. The preparation method according to claim 4, characterized in that: The carrier is obtained by the following preparation method: fully mixing the aluminum source, the molding agent, the pore expanding agent and the functional carbon, adding the binder, kneading and molding, drying, and then performing surface treatment to obtain the carrier.

7. The preparation method according to claim 6, characterized in that: In the preparation method of the carrier: The aluminum source is selected from at least one of boehmite, pseudo-boehmite, γ-alumina, α-alumina, θ-alumina, and aluminum hydroxide; and / or, The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch; and / or, The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide and polypropylene glycol; and / or, The functional carbon is selected from at least one of coke, activated carbon, carbon black, white carbon, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; and / or, The binder is selected from a solution of at least one of nitric acid, sulfuric acid, hydrochloric acid, oxalic acid, acetic acid, citric acid and ascorbic acid, and the solvent in the solution is selected from at least one of water, ethanol, ethylene glycol and ethylenediamine; and / or, The amount of the functional carbon is 1 to 40 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained; and / or, The amount of the forming agent used is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained; and / or, The amount of the pore expanding agent used is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the contained Al2O3.

8. The preparation method according to claim 6, characterized in that: In the preparation method of the carrier: The drying conditions are: drying at 60-160°C for 4-12 hours, preferably, drying at 80-140°C for 6-10 hours; and / or, The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization and irradiation.

9. The preparation method according to claim 8, characterized in that: The heat treatment conditions are as follows: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; and / or, The crystallization conditions are: temperature 120-250° C., time 4-18 h, pressure 0.2-15 MPa, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine; and / or, The oxidation conditions are: temperature 30-80°C, time 0.2-10h, the oxidant solution used for oxidation is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L; and / or, The alkalization conditions are: temperature 30-110° C., time 0.2-10 h, the alkaline solution used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline solution is 0.1-10 mol / L; and / or, The irradiation conditions are: the ray source is selected from gamma rays and / or microwaves, preferably, the gamma ray irradiation dose rate is 1-90 kGy / min, the time is 0.2-24 h; and / or the microwave power is 50-1000 W, the time is 0.5-60 min.

10. Use of the acetylene selective hydrogenation catalyst according to any one of claims 1 to 3 or the acetylene selective hydrogenation catalyst obtained by the preparation method according to any one of claims 4 to 9 in the selective hydrogenation reaction of carbon distillation.

11. The use according to claim 10, characterized in that: In the hydrogenation reaction, the molar ratio of H2 to alkynes in the carbon distillation feedstock is (1.2-2):1, preferably (1.3-1.6):1; and / or, The conditions of the hydrogenation reaction include: reactor inlet temperature of 25-85°C, reactor pressure of 0.5-3.2 MPa, reaction space velocity of 2000-12000 h -1 .

Citation Information

Patent Citations

  • Method for preparing hydrogenation catalyst

    CN102240565A

  • Preparation method of high-coking resistance selective-hydrogenation catalyst

    CN104096573A

  • Fe series selective hydrogenation catalyst, and preparation method and application thereof

    CN106925272A

  • Alumina carrier as well as preparation method and application thereof

    CN119500087A

  • Method for selective hydrogenation of pyrolysis gas

    CN102220168A